2016
DOI: 10.1037/a0039442
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the Partner Cyber Abuse Questionnaire in a college student sample.

Abstract: Objective To examine the factor structure and convergent validity of a newly developed measure of an understudied form of partner abuse, cyber abuse, and to examine the prevalence of, and gender differences in, victimization by cyber abuse. Method College students in a dating relationship (N = 502) completed the Partner Cyber Abuse Questionnaire (Hamby, 2013), as well as measures of partner abuse victimization and depression. Results Using exploratory factor analysis, we determined a one-factor solution wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 34 publications
7
62
0
9
Order By: Relevance
“…There is an empirical literature exploring technologyfacilitated violence, but to date it has mostly focused on "electronic dating violence" among high school and college groups in the Global North (Borrajo, Gámez-Guadix, Pereda, & Calvete, 2015;Dick et al, 2014;Hinduja & Patchin, 2011;Lucero, Weisz, Smith-Darden, & Lucero, 2014;Reed, Tolman, Ward, & Safyer, 2016;Temple et al, 2016;Watkins, Maldonado, & DiLillo, 2018;Wolford-Clevenger et al, 2016;Zweig, Dank, Yahner, & Lachman, 2013). Another body of research centers on "social media surveillance" (J.…”
mentioning
confidence: 99%
“…There is an empirical literature exploring technologyfacilitated violence, but to date it has mostly focused on "electronic dating violence" among high school and college groups in the Global North (Borrajo, Gámez-Guadix, Pereda, & Calvete, 2015;Dick et al, 2014;Hinduja & Patchin, 2011;Lucero, Weisz, Smith-Darden, & Lucero, 2014;Reed, Tolman, Ward, & Safyer, 2016;Temple et al, 2016;Watkins, Maldonado, & DiLillo, 2018;Wolford-Clevenger et al, 2016;Zweig, Dank, Yahner, & Lachman, 2013). Another body of research centers on "social media surveillance" (J.…”
mentioning
confidence: 99%
“…Wolford‐Clevenger et al. () compared the factor structure and validity of the CPA and the Partner Cyber Abuse Questionnaire (PCAQ) and found that the PCAQ appears to assess the use of technology in more controlling abuse while the CPA assesses both minor verbal and severe controlling abuse. At the same time, mixed correlations between the PCAQ and other forms of partner abuse suggested both similarities and differences between online and offline forms of abuse.…”
Section: Development Of Scales For Measuring Cyber Abuse In Intimate mentioning
confidence: 99%
“…A small number of US studies have developed measures for assessing the psychological aspects of cyber abuse with particular populations (Leisring & Giumetti, ; Watkins, Maldonado, & DiLillo, ; Wolford‐Clevenger et al., ). Furthermore, there are a number of legal cases beginning to emerge where material published on Facebook and other online sites is used to embarrass, humiliate, denigrate, belittle, terrorise, or otherwise cause harm to one party in the context of relationship breakdown (Baughman, ; Blakeley, Easteal, Fitch, & Kennedy, ; Lackey & Mae, ; Xuarez & Vitela, ).…”
mentioning
confidence: 99%
“…In one of the first studies of cyber dating abuse, Picard (2007) found that a quarter of teenagers had a boyfriend or girlfriend that called them names, put them down, or said "really mean things" through technology. Over 30% of college students reported that their partners had sent angry or insulting text messages to them (Wolford-Clevenger et al 2016). Partners may also swear at their significant others through email, text messages, or social media, and they may "shout" at one another by sending messages with all capital letters (Leisring and Giumetti 2014).…”
Section: Types Of Cyber Abuse That Occur Within Romantic Relationshipmentioning
confidence: 99%
“…Technology provides a way for one individual to track another via GPS, have access to social media accounts without the owner's permission, and to otherwise monitor their partner's behavior in an invasive way (Marganski and Melander 2018). Cyber monitoring and surveillance (i.e., cyberstalking) often serves to aid in controlling the other person in a romantic relationship (Marganski and Melander 2018;Reed et al 2016b;Wolford-Clevenger et al 2016). The perpetrator may experience an immediate need to obtain information on the whereabouts and activities of the other individual (Marcum et al 2017).…”
Section: Intrusion/monitoring/stalking Behaviorsmentioning
confidence: 99%